Model predictive control-based energy management system with load curtailment for standalone microgrid - Mohd Yunus, Muhammad Sharir Fathullah; Yusoff, Siti Hajar; Mohd Sapihie, Siti Nadiah; Abu Hanifah, Mohd Shahrin; Gunawan, Teddy Surya; Zabidi, Suriza Ahmad (IIUM Press, 2025)
The standalone microgrid emerges as an economical solution for providing electricity to remote areas disconnected from the main grid. However, the intermittent nature of renewable energy sources (RES) and unpredictable load demands can disrupt its balance. Diesel generators are commonly used to supply auxiliary power and serve as a backup for the microgrid. Nevertheless, inefficient utilization of diesel generators can lead to high operational costs, shortened lifespan, and environmental pollution. An energy management system (EMS) is implemented to optimize the operational cost and reliability of the microgrid by incorporating model predictive control (MPC), which has grown in popularity in recent years due to its ability to support multiple inputs and multiple outputs. The MPC-based EMS is developed using MATLAB/Simulink software, with the optimization problem formulated using mixed integer quadratic programming (MIQP). A comparative analysis is conducted between the MPC-based EMS with and without load curtailment capability, revealing a significant improvement of 52.21% in diesel fuel cost savings with the inclusion of load curtailment capability